This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using the identity 2 sin ( a ) cos ( b ) = sin ( a − b ) + sin ( a + b ) with a = 3 0 ∘ and b = 1 0 ∘ we see that
sin ( 2 0 ∘ ) + sin ( 4 0 ∘ ) = sin ( 3 0 ∘ − 1 0 ∘ ) + sin ( 3 0 ∘ + 1 0 ∘ ) = 2 sin ( 3 0 ∘ ) cos ( 1 0 ∘ ) = cos ( 1 0 ∘ )
since sin ( 3 0 ∘ ) = 2 1 . But as cos ( θ ) = sin ( 9 0 ∘ − θ ) we know that cos ( 1 0 ∘ ) = sin ( 8 0 ∘ ) , and so the given expression is E = 1 , giving us a desired answer of ⌊ 1 0 0 0 E ⌋ = 1 0 0 0 .